2022
DOI: 10.1080/07370024.2022.2050725
|View full text |Cite
|
Sign up to set email alerts
|

Playing during a crisis: The impact of commercial video games on the reconfiguration of people’s life during the COVID-19 pandemic

Abstract: The COVID-19 pandemic led to dramatic changes in people's lives. The Human-Computer Interaction (HCI) community widely investigated technology use during crises. However, commercial video games received minor attention. In this article, we describe how video game play impacted the life transformations engendered by the pandemic. We administered a qualitative online survey to 330 video game players who were living in Italy during the lockdown measures. We found that the COVID-19 pandemic altered the participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 194 publications
(240 reference statements)
0
19
0
2
Order By: Relevance
“…Notwithstanding, extensive time spent gaming could also replace or influence in-person interactions, which could in turn compromise existing relationships (Shen & Williams, 2011). Escaping to a virtual world may also provide youth with a fun and adventurous space that may relieve stress (Barr & Copeland-Stewart, 2022) and help keep potential worries concerning the pandemic away (Boldi et al, 2022). Indeed, results from studies conducted before the pandemic have suggested that gaming can reduce symptoms of psychopathology, including symptoms of anxiety (Hygen, Skalická, et al, 2020) and depression (Russoniello et al, 2013).…”
Section: Differential Communication Functions Of Various Digital Mediamentioning
confidence: 99%
“…Notwithstanding, extensive time spent gaming could also replace or influence in-person interactions, which could in turn compromise existing relationships (Shen & Williams, 2011). Escaping to a virtual world may also provide youth with a fun and adventurous space that may relieve stress (Barr & Copeland-Stewart, 2022) and help keep potential worries concerning the pandemic away (Boldi et al, 2022). Indeed, results from studies conducted before the pandemic have suggested that gaming can reduce symptoms of psychopathology, including symptoms of anxiety (Hygen, Skalická, et al, 2020) and depression (Russoniello et al, 2013).…”
Section: Differential Communication Functions Of Various Digital Mediamentioning
confidence: 99%
“…Many concerns were raised about whether players would increase their gaming time and, in turn, decrease their well-being and increase adverse outcomes such as depression or anxiety (Xu et al, 2021). In contrast, some argued that increased gaming during a pandemic might be an effective strategy to facilitate mental health in a restrictive physical environment, e.g., by providing high-quality entertainment, stress relief, and social interaction opportunities with other players (Boldi et al, 2022;Giardina et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, accumulated evidence has shown that the COVID-19 pandemic has generated or worsened psychological symptoms [3], including depression and anxiety [4], and stress [5]. In such a challenging period, online activities offered some relief, helping both adolescents and adults to stay in contact with loved ones and mitigate the emotional impact of isolation measures in several meaningful ways [6,7]. For example, Barr and Copeland-Stewart [8] documented a change in how and why people played games during the pandemic and the ways it affected well-being.…”
Section: Introductionmentioning
confidence: 99%